ANALISA PENGARUH RADIUS POJOK (nsr) TERHADAP KEAUSAN TEPI PAHAT (Vb) DITINJAU DARI MORFOLOGI KARAKTERISTIK KEAUSAN - Sudjatmiko Sudjatmiko; Darto Darto; Abdur Rabi' (INFO-TEKNIK, 2017)
The magnitude of the corner radius (nsr), the cutting speed (V), the feeding motion (f), and the cutting depth (cut depth), will offend the cutting edge wear (Vb) and the quality of the finished product with Al 6061-T6. The problem of the effect of a large corner radius (nsr) on wear and tear. (Vb) on the Lathe process which affects the quality of the product. Research Objectives to produce the following wear results (Vb) on the quality of the lathe products; It produces the characteristics of the chisel root wear (Vb). Benefits Research to know benchmark tobacco (Vb) benchmarks on the quality of the lathe products, and the wear and tear feature of wear (Vb) and benchmarks. The results achieved in the feeding motion have a significant effect on the wearing of the chisel roots (Vb), evidenced by the presumption of the equation y = Vb (Um) = -0.00105 + 0.000186 f (mm / put). The value of surface roughness (SR) is evidenced by the assumption of equation y = SR (Um) = -5.22 + 0.00440 n (Put / min) + 5.55 nsr (mm) + 0.0660 f (mm / put0.000002 n (Put / min) * N (Put / min) - 0.0814 nsr (mm) * f (mm / put) Response response at rotation (n) 750 put / min, corner radius (nsr) 0.4 mm and feeding motion (f) 80 mm / Input to the surface roughness value (SR) 1.010 μm, cutting edge wear (Vb) 0,1536 μm Morfologi wear cutting edges with above condition no BUE (edge bush) so no abrasive, adhesion and Flaking occur, Chiping in the field of anger and the main plane, so stacking the corner radius (nsr) is very small also affects the decrease of product quality quality.Response growth at round (n) 1000 put / menit, corner radius (nsr) 0.4 mm and feeding motion (F) 70 mm / put surface roughness results (SR) 1.085 μm, cutting edge wear (Vb) 0.1210 μm Morphology of upper edge wear occurrence of BUE (bult edge up) embodiment of abrasive, adhesive I, diffusion and flaking, Chiping in the field of anger and the main field, so translating the corner radius (nsr) in the main field, the impact on the decrease of product quality.